Tribological Mechanism of Friction and Wear Reduction Using Oil-Based ZnO Nanofluid Applied on Brass - Tao, Chuanlin; Wang, Bingxu; Barber, Gary C.; Schall, J. David; Zou, Qian; Wang, Jing (European Scientific Journal, ESJ, 2019)
In this research, friction and wear characteristics of oil-based ZnO nanofluid applied on brass disk specimens using a flat-on-flat reciprocating sliding test were studied. Oleic acid was used as surfactant to improve the stability and dispersibility of the ZnO nanofluid. Metallurgical optical microscopy, scanning electron microscopy and energy-dispersive X-ray spectroscopy were utilized to understand the mechanisms. A 2wt% ZnO nanofluid resulted in 61.1% reduction in coefficient of friction. Good wear resistance was achieved using low concentrations of 0.5wt% and 1wt% ZnO nanofluid. A tribo-film mainly composed of carbon was found inside the wear track, which enhanced the wear resistance and lowered the interface shear strength. This tribo-film was produced by oleic acid which was chemically adsorbed to the brass materials.